DERADICALIZATION OF RELIGION IN SUMENEP DISTRICT: (The Gait of NU and Muhammadiyah Youth Organizations In Countering Religious Radicalism) - Basri, Hasan; Alam, Suluh Mardika (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2022)
Deradicalization is the main strategy of the Indonesian government in countering terrorism in Indonesia. This effort is embedded in the main task of the National Counterterrorism Agency (BNPT). Throughout 2017, there were 172 suspects in terrorism cases. This number is higher than in the previous two years, namely 163 in 2016 and 73 in 2015. Sumenep is one of the districts on the eastern tip of the island of Madura where the majority of its citizens are Muslims. members of Jamaah Islamiyah (JI) (Kompas daily 11 November 2021. The arrest of the alleged terrorists certainly captured a lot of public attention, including the largest religious organizations in Sumenep district, namely NU and Muhammadiyah. The purpose of this study was to find out how the progress of 2 religious organizations was This research uses qualitative research with a phenomenological approach, with primary and secondary data sources and uses data collection procedures of observation, interviews and documentation. The results obtained from the research are that the Nahdlatul Ulama and Muhammadiyah social organization movements with their ideological basis and da'wah methods have a significant role in tackling radicalism movements, so that society in general can be protected from these movements, as well as structural and cultural forces that intensively guard social life.